Trichosporon asahii ankle cavity effusion infection in a patient with severe aplastic anemia - Peng Zhang; Zhenghai Yang; Jie Li; Xiaoning Li (Asian Pacific Journal of Tropical Medicine, 2020)
Rationale: Trichosporon, an anamorphic fungus, proliferates under high humidity, causing serious opportunistic infections collectively called trichosporonosis. Among the Trichosporon species causing trichosporonosis are Trichosporon (T.) asahii, T. asteroides, T. cutaneum etc. Patient concerns: A 38-year-old Chinese male with severe aplastic anemia was admitted due to multiple joints pain, poor appetite, and right ankle swelling. One year earlier he had undergone allogeneic hematopoietic stem cell transplantation. Diagnosis: T. asahii infection and severe aplastic anemia. Interventions: Combined treatment of amphotericin B liposomes (55 mg/24 h) and voriconazole (200 mg/12 h) for 8 days. Outcomes: The symptoms of the patient’s ankle were relieved and effusion cultures showed no T. asahii. Lessons: To the best of our knowledge, T. asahii ankle cavity effusion infections are rare. Trichosporon infections may be attributed to risk factors such as improper long-term use of antimicrobials for an underlying disease (e.g., anemia, hypoalbuminemia). Attention should be paid to prevent and control Trichosporon infections in order to avoid comorbidities.